Phylointeractomics reconstructs functional evolution of protein binding - Dennis Kappei (Nature Portfolio, 2017)
Since protein interactions can be sensitive to small sequence changes, phylogenomics alone gives limited insight into protein functional evolution. Here, the authors illustrate how the combination of phylogenomics and interaction proteomics helps elucidate protein functional evolution with a study of the shelterin complex evolution.